Empowering Women through Self-Help Groups -A Case Study ofFatehabadDistrictofHaryana. - Dhiman, Pawan Kumar; Amita, (Gyan Management Journal, 2010)
In India women are among the most vulnerable and marginalized group in the world of work. Almost two fifth of its population lives below poverty line. In India, when a man is working 391 minutes woman is working 457 minutes a day. According to 2001 census the average age of the entire female worker was 33.6 as compared with the male average of36.5 and the participation of women in the labour force has always been lower than that of man in the rural as well as urban areas. Still they are considered as an uncontributory towards the national growth because they are unskilled, unorganized and financially dependent upon male. As a result they are unable to convert their dreams into reality although they have entrepreneurial potential. Realizing their backwardness the Government of India has launched number of schemes such as: Swarna jayanti Gram Swarozgar Yojana, (SGSY), Development of Women and Children in Rural areas (DWCRA), Integrated Rural Development Programme {IRDPJ, Supply of Improved tool kits to Rural Artisan (SITRA) etc. The SGSY has been introduced with a clear objective to establish large number of micro enterprises in rural areas and to uplift the socio economic standard of the poor through Self-Help Groups (SH Gs). In some of the states these groups are doing well in SH Gs activities whereas many states are not performing due to many reasons. The present paper is an attempt to find out the performance of SH Gs in Fatehbad district of Haryana. It has been found that SHGs are not performing as per expectations only few SH Gs are actively involved in SH Gs activities, some has just got first installment whereas majority of the groups has not taken even a single penny to start their activities, and some are availing the subsidy and not taking keen interest to generate employment and revenue.
Keywords: marginalized group; population; SGSY; IRDPJ; SITRA